Internet of things (IoT) device for web based river’s velocity monitoring / Mohd Radzuan Othman - Othman, Mohd Radzuan (2020)
An estimated of 372,000 people died of drowning in 2012, making it the third largest unintentional injury killer in the world. In Malaysia, the death rate due to drowning has steadily increased. Every year, approximately 700 cases of drowning are reported, or about two people die every day in bodies of water. The primary location of drowning in Malaysia is the river, beach and waterfall. However currently, the reality in Malaysia is that there are no channels or sources of real time information that can be accessed by the general public or rescue teams about information on the rivers velocity. Malaysians observe these areas to decide whether the place is safe or dangerous. The warning system of the river velocity stream is using improper a warning notices and red flags at specific locations. Hence, this project proposes to develop a prototype system that can measure the river velocity, determine the danger of the river and publish the information online. The prototype developed was tested with sensitivity and functionalities test. Prototype developed using water flow sensor to measure water flow and using Arduino Nodemcu to calculate the velocity and sent it to Thing Speak and a web site through internet The results show that this prototype is able to measure the velocity, determine whether the velocity is dangerous and provide this information to be stored in ThingSpeak database. The system is able to display that information on website. The usability results shows that the 100% of respondence is agree this project is implemented and able to prevent drowning. Indirectly reduces the drowning index.